A comprehensive overview of PPM1A: From structure to disease. Issue 6 (March 2022) - Li, Mao; Xu, Xingfeng; Su, Yan; Shao, Xiaoyun; Zhou, Yali; Yan, Jianguo
PPM1A (magnesium-dependent phosphatase 1 A, also known as PP2Cα) is a member of the Ser/Thr protein phosphatase family. Protein phosphatases catalyze the removal of phosphate groups from proteins via hydrolysis, thus opposing the role of protein kinases. The PP2C family is generally considered a negative regulator in the eukaryotic stress response pathway. PPM1A can bind and dephosphorylate various proteins and is therefore involved in the regulation of a wide range of physiological processes. It plays a crucial role in transcriptional regulation, cell proliferation, and apoptosis and has been suggested to be closely related to the occurrence and development of cancers of the lung, bladder, and breast, amongst others. Moreover, it is closely related to certain autoimmune diseases and neurodegenerative diseases. In this review, we provide an insight into currently available knowledge of PPM1A, including its structure, biological function, involvement in signaling pathways, and association with diseases. Lastly, we discuss whether PPM1A could be targeted for therapy of certain human conditions.